Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/6207457
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors Associated with Knowledge on Tuberculosis among Adults in Ethiopia

Abstract: Background. Ethiopia is among highly tuberculosis affected countries. This might be related to low level of awareness on the disease in the population. The objective of the study was to determine the level of tuberculosis knowledge and socioeconomic factors associated with it. Methods. The 2011 Ethiopia health and demographic survey data were used. Overall tuberculosis knowledge score was computed to evaluate the outcome variable. Multivariable logistic regression was employed to identify independent socioecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 18 publications
(21 reference statements)
8
40
1
Order By: Relevance
“…Findings from current study also revealed that patients' knowledge is associated with gender and age, these findings are in line with some studies. [19,[30][31][32] However, contrary to our findings, other studies [17,29] reported no association between patients' knowledge of TB and mentioned demographic factors (age and gender).…”
Section: Discussioncontrasting
confidence: 99%
“…Findings from current study also revealed that patients' knowledge is associated with gender and age, these findings are in line with some studies. [19,[30][31][32] However, contrary to our findings, other studies [17,29] reported no association between patients' knowledge of TB and mentioned demographic factors (age and gender).…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, 41.85% of migrant and seasonal farm workers were knowledgeable. This finding was in line with the finding from EDHS 2011 (44.14%) (17). However, the finding was lower than a study conducted in Lesotho (59.9%) (21)and Zimbabwe (73.8%) (22).…”
Section: Discussionsupporting
confidence: 90%
“…Addressing knowledge gaps in TB prevention has a great role in eliminating TB (5). Literacy (6, 7), gender (6), mass media (8-10), being a TB patient (11), professional occupation (7,12), health education (13), culture myths (14,15), knowledge (16), wealth index (17), age (18), and residence (19) were some of the factors affecting knowledge and attitude. Since knowledge is a precursor of a TB control strategy, determining knowledge of migrants and seasonal farm workers is very crucial in enabling and fastening controlling TB strategies (20).…”
Section: Introductionmentioning
confidence: 99%
“…Eq (2): Disease knowledge is believed to be determined primarily by education and higher wealth from increased access to information through multiple channels such as television, radio and social media [10,12,17,52,54]. Sex also tends to play a role on knowledge: a study demonstrated that women had 63% higher odds of being able to correctly cite at least three dengue symptoms [17].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%